Effect of Thermal Treatment on Fractals in Acoustic Emission of Rock Material - Z. Z. Zhang; X. L. Xu; Q. P. Sun; Y. Dong (Advances in Materials Science and Engineering)
Acoustic emission (AE) series on time and location distributions on space are all fractal during the failure process of rock material. In this paper, AE signals of heated rock samples at different temperature under uniaxial compression were captured, and the correlation fractal dimensions (CFDs) of AE counts series at different stress level were calculated using Grassberger-Procaccia algorithm. The temperature effect on AE fractal behavior was revealed. The results show that as the heat temperature increases, the total AE counts are more, while the peak value is less. With the increase of external loading, the AE CFD increases fast to a peak at first and then decreases to a bottom and, after that, increases again but within a narrow range. 200°C and 800°C are two thresholds. As the heat temperature rises, the maximum CFD value and the corresponding stress level both increase from 25°C to 200°C and decrease from 200°C to 800°C and then increase again from 800°C to 1200°C. The CFD value at the failure point shows polynomial decline with rising heat temperature.